2012
DOI: 10.3390/ijms131012952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of White Rice, Brown Rice and Germinated Brown Rice on Antioxidant Status of Type 2 Diabetic Rats

Abstract: Oxidative stress is implicated in the pathogenesis of diabetic complications, and can be increased by diet like white rice (WR). Though brown rice (BR) and germinated brown rice (GBR) have high antioxidant potentials as a result of their bioactive compounds, reports of their effects on oxidative stress-related conditions such as type 2 diabetes are lacking. We hypothesized therefore that if BR and GBR were to improve antioxidant status, they would be better for rice consuming populations instead of the commonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 35 publications
8
60
0
1
Order By: Relevance
“…They showed that germinating BR in tap water at 25°C significantly improved total phenolic content of BR and antioxidant activities as determined by DPPH and ABTS radical scavenging activity and ferric reducing antioxidant power ( P < 0.05). Others have also reported similar findings [22, 23, 30, 35, 40]. Jiamyangyuen and Ooraikul [59] had reported also that GBR had lower amylose content consistent with reports in which activation of amylase enzyme was responsible for higher amounts of bioactives in GBR [60].…”
Section: Germination Of Brown Ricesupporting
confidence: 78%
“…They showed that germinating BR in tap water at 25°C significantly improved total phenolic content of BR and antioxidant activities as determined by DPPH and ABTS radical scavenging activity and ferric reducing antioxidant power ( P < 0.05). Others have also reported similar findings [22, 23, 30, 35, 40]. Jiamyangyuen and Ooraikul [59] had reported also that GBR had lower amylose content consistent with reports in which activation of amylase enzyme was responsible for higher amounts of bioactives in GBR [60].…”
Section: Germination Of Brown Ricesupporting
confidence: 78%
“…1(B), EBN produced a hormetic effect on the viability of the cells in the presence of H 2 O 2 , with 1000 μg/ml EBN producing the best result. Although antioxidants are known to relieve oxidative stress and improve cell survival, it is also suggested that higher concentrations of antioxidants may in fact disrupt the natural hormetic capacity of cells 21) resulting in more damage. It is also likely that at higher concentrations, the oxidants simply became prooxidant.…”
Section: Lf and Ovf Detection In Ebn Water Extractionmentioning
confidence: 99%
“…While, non-germinated rice showed 3.17 ± 1.68, 2.67 ± 0.24, and 6.82 ± 0.23 of total phenolic content, ABTS, and DPPH activity, respectively (Imam et al, 2012). The phenolic and flavonoid contents increased in germinated jasmine rice (KDML105) (Phattayakorn et al, 2016).…”
Section: Phytochemical Content Of Germinated Black Rice (Gbr)mentioning
confidence: 99%